America in the Progressive Era, 1890-1917 - Gould, Lewis L., author.
1 online resource
Keywords: "Now in its second edition, American in the Progressive Era, 1890-1917 provides a readable, analytical narrative of the emergence, influence, and decline of the spirit of progressive reform that animated American politics and culture around the turn of the twentieth century. Covering the turbulent 1890s to the American entry into World War I, the text examines the political, social, and cultural events of a period which set the agenda for American public life during the remainder of the twentieth century. This new edition places progressivism in a transatlantic context and gives more attention to voices outside the mainstream of party politics. Key features include: A clear account of the continuing debate in the United States over the role of government, citizenship, and the pursuit of social justice A full examination of the impact of reform on women and minorities A rich selection of documents that allow the historical actors to communicate with today's readers An extensive, updated bibliography providing a valuable guide to additional reading and research Based on the most recent scholarship and written to be read by students, this book will be of interest of students of American History and Political History"--